Behavior of steel–concrete composite bolted connector in precast reinforced concrete shear wall. Issue 12 (September 2019) - Jiang, Hongbo; Qiu, Hongxing; Sun, Jian; Yang, Yuan
An assembling method of precast shear walls was previously proposed using steel–concrete composite bolted connectors. To further investigate the effectiveness and mechanical behavior of the proposed composite connector, 11 specimens were fabricated and tested under monotonic tensile loading. The test results provided comprehensive data (e.g. load, deformation, failure mode) on the effects of variation in the thickness of steel cap plate, concrete strength, bolt tension, and bolt diameter. Two typical failure modes were observed in the test: bearing failure and bolt shear failure. Finally, the equations for calculating the ultimate strength and yield strength of steel–concrete composite bolted connector are proposed in this article by reference to those of conventional bolted connection. The proposed calculations are demonstrated to be accurate enough through verification with the experimental data.